Aktivasi Bottom Ash dari Pembakaran Batubara untuk Menurunkan Kandungan Senyawa Fosfat dalam Air - Fatimah; Pratama Tarigan, Budi; Ramadhan , Alfikri (Jurnal Teknik Kimia USU, 2019)
This study aims to look at the effect of bottom ash activation with NaOH on the morphological structure and content of the elements contained in bottom ash and see the effect of activation on the absorption of phosphate compounds in water by bottom ash. Bottom ash from PT SOCIMAS coal combustion has been activated with NaOH and has been used to adsorb phosphate. Phosphate used in the form of KH3PO4. Bottom ash was first characterized by SEM-EDS to see the morphological structure and the element content contained in the bottom ash. Bottom ash mass variations used are (1, 2, and 3 grams), and particle size (50-70 mesh, 70-110 mesh, and 110-140 mesh). The activation process lasts for 5 hours using 3 M NaOH, then washed to pH 7. The bottom ash is activated then characterized again with SEM-EDS to ensure the impurities present in the bottom ash are reduced. Furthermore, bottom ash is used to adsorb phosphate with time variations of 20, 40, and 60 minutes. The most effective adsorption capacity (6.39 mg / g) is at the 20th minute with a particle size of 110-140 mesh and a bottom ash mass of 1 gram. The Freundlich and Langmuir isotherm model is used to describe the phosphate ion adsorption isotherm by the bottom ash. Based on the data obtained, the isotherm model suitable for this research is the Freudlich (R2 = 0.9721) and Langmuir (R2 = 0.9505) isotherm model.